2022
DOI: 10.1186/s12891-022-05581-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of a 3D-printed arthrodesis prosthesis for reconstruction after resection of the proximal humerus: preliminary outcomes with a minimum 2-year follow-up

Abstract: Background The purpose of this study was to investigate the feasibility of using a three-dimensional (3D)-printed arthrodesis prosthesis for reconstruction of the proximal humeral defect after tumor resection. Methods A novel proximal humeral prosthesis was designed to restore bone continuity and shoulder arthrodesis and was fabricated via 3D printing technology. Ten patients with primary malignancies in the proximal humerus underwent intra-articul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Liang, et al (2022) 14 showed the mean MSTS-93 score were 24.9±3.1. The mean forward flexion and abduction angles were 71.3 ± 19.4° and 61.3 ± 16.4°, respectively.…”
Section: Complicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Liang, et al (2022) 14 showed the mean MSTS-93 score were 24.9±3.1. The mean forward flexion and abduction angles were 71.3 ± 19.4° and 61.3 ± 16.4°, respectively.…”
Section: Complicationsmentioning
confidence: 97%
“…Liang, et al (2022) 14 showed that two cases (20.0%) experienced detachment at the taper. One patient was disease-free and refused further operations for reduction of the prosthesis, while the other patient also had tumor recurrence and was treated by forequater amputation.…”
Section: Complicationsmentioning
confidence: 99%
“…23 In addition, unique implants have been created for shoulder arthrodesis after tumor resection, elbow hemiarthroplasty (both on the humeral and ulnar side) for bone loss, and even total humerus or radius replacement. 18,[24][25][26] Case 3…”
Section: Arthroplasty/intraarticular Applicationsmentioning
confidence: 99%
“…4 Modular proximal humerus endoprosthetic replacement (PHER) has emerged as a preferred reconstruction approach after tumor resection due to its convenience, good cosmetic appearance, and acceptable limb functions. 1,5,6 Despite continuous improvements in implant design, a high failure rate was reported regarding the reconstruction of the proximal humerus with PHER, (14%-45%). [7][8][9] Soft tissue failure is the most common failure mode, while aseptic loosening is considered to be rather uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in oncology, imaging, and surgical technologies have enabled limb salvage surgery to be the standard treatment 4 . Modular proximal humerus endoprosthetic replacement (PHER) has emerged as a preferred reconstruction approach after tumor resection due to its convenience, good cosmetic appearance, and acceptable limb functions 1,5,6 . Despite continuous improvements in implant design, a high failure rate was reported regarding the reconstruction of the proximal humerus with PHER, (14%–45%) 7–9 .…”
Section: Introductionmentioning
confidence: 99%